Risk of Reactivation of Latent Tuberculosis in Psoriasis Patients on Biologic Therapies: A Retrospective Cohort from a Tertiary Care Centre in Northern Italy - Luca Mastorino; Paolo Dapavo; Mattia Trunfio; Gianluca Avallone; Marco Rubatto; Andrea Calcagno; Simone Ribero; Pietro Quaglino (Medical Journals Sweden, 2022)
Psoriatic patients with latent tuberculosis infection and properly treated active tuberculosis need careful management when prescribing modern biological drugs. Although data and guidelines regarding tumour necrosis factor-α inhibitors advise caution and initiation of prophylactic therapy in patients with latent tuberculosis infection, the same indications do not seem to find equal force for interleukin (IL)-23 and IL-17 inhibitors. In order to evaluate the risk of reactivation in patients with latent tuberculosis infection or properly treated active tuberculosis, an observational retrospective study was conducted on the population referred to our centre at Dermatologic Clinic of University of Turin, Italy. In the last 10 years at the clinic 19 psoriatic patients were found to be at risk of tuberculosis reactivation: 10 patients were QuantiFERON- TB-positive at baseline, 2 became positive during treatment, 6 reported prior tuberculous infection, and 1 was QuantiFERON-TB-negative at baseline and developed disseminated tuberculosis during treatment with anti-tumour necrosis factor-α. Overall, 10.5% of this group of patients developed active tuberculosis; however, stratifying by biologic therapy, zero cases were observed among patients treated with anti-IL-17, -23, or -12/23 over a relatively long follow-up (48.1 months) A review of the available literature following our experience confirms the increased risk of tuberculosis reactivation with tumour necrosis factor-α inhibitors. Concerning anti-IL-23 and IL-17 drugs, available data showed high safety in patients at risk of tuberculosis reactivation. Screening of patients who should be taking IL-17 and IL-23 inhibitors is recommended for public health purposes. In case of a positive result with these therapies, consulting with an infectious diseases specialist is suggested in order to weigh up the risks and benefits of prophylactic treatment.